THE PECULARITIES OF THE ECOLOGICAL COMPETENCE STRUCTURE OF FUTURE MASTERS OF INDUSTRIAL TRAINING OF CONSTRUCTION PROFILE - Osadcha, M. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. Contemporaneity demands the appliance of the new forms and standards as for the environmental component on the high school. Today the formation of ecological competence in combination with getting a profession during the high school studying is being important. Just the formation of ecological competence of future industrial training masters in general, is the extremely important process through the modern students are responsible for the level of ecological and orientation of their pupils in future. Despite the numerous publications the given research topic is not fully investigated. Purpose. Allocation and justification of the structural components of ecological competence of future industrial training masters of construction profile in the process of professional training clarification of criteria, parameters and indices of moulding of every of them. Results. The attention is accentuated on the problem of forming of ecological competence of future industrial training masters. The development of construction sphere, particularly, puts a priority on environmental issues. During the process of the professional training there formed the ecological competence of future specialists. The given competence is especially important for the masters of industrial training. In the investigation mrerhed the separate structural components of ecological competence of future industrial training masters of construction profile: cognitive-intellectual, emotional-valuable, activity-behavioral. The criteria, parameters, definitions of given structures are defined more exactly. Originality. Due to the analysis there created the structure of ecological competence of future industrial building masters of construction profile for the first time. Three components are input to the composition of the: cognitive-intellectual, emotional-valuable, activity-behavioral. Scientific conception about the essence structure of the process of formation of ecological competence of masters of industrial training of construction profile, the notion “the masters of industrial building”. Conclusion. We analized the literature of psychology and pedagogics and determine the components of ecological competence of future masters of industrial training of construction profile (cognitive-intellectual, emotional-valuable, activity-behavioral). There also determine the criteria, parameters and definitions of above mentioned components. The results given due to the investigation are recommended to use in the organization and the diagnostics of the process of formation of ecological competence of the above-mentioned category of specialists. The study does not cover all aspects of the problem. That is why further investigation will be oriented on the definition of the level of moulding of ecological competence of students.